A Cognitive Style Perspective to Handheld Devices: Customization vs. Personalization - Hsieh, Chen-Wei; Chen, Sherry Y. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Handheld devices are widely applied to support open and distributed learning, where students are diverse. On the other hand, customization and personalization can be applied to accommodate students’ diversities. However, paucity of research compares the effects of customization and personalization in the context of handheld devices. To this end, a customized digital learning system (CDLS) and personalized digital learning system (PDLS) were implemented with the handheld devices and they tailored to the needs of different cognitive style groups. Furthermore, we conducted two empirical studies to examine the effects of cognitive styles on the use of the CDLS and PDLS. More specifically, Study 1 identified the preferences of each cognitive style group while Study 2 investigated how students with different cognitive styles react to the CDLS and the PDLS. The results from these two studies showed that student with the CDLS and those with the PDLS obtained similar task scores and post-test scores, regardless of their cognitive styles. However, cognitive styles affected the efficiency of completing tasks and perceptions for customization and personalization.